Effects of environmental noise on cognitive (dys)functions in schizophrenia: A pilot within-subjects experimental study - Wright, Bernice (Schizophr Res, 2016)
Cognitive impairment, particularly in attention, memory and executive function domains, is commonly present and associated with poor functional outcomes in schizophrenia. In healthy adults, environmental noise adversely affects many cognitive domains, including those known to be compromised in schizophrenia. This pilot study examined whether environmental noise causes further cognitive deterioration in a small sample of people with schizophrenia. Eighteen outpatients with schizophrenia on stable doses of antipsychotics and 18 age and sex-matched healthy participants were assessed on a comprehensive cognitive battery including measures of psychomotor speed, attention, executive functioning, working memory, and verbal learning and memory under three different conditions [quiet: ~ 30 dB(A); urban noise: building site noise, 68–78 dB(A); and social noise: background babble and footsteps from a crowded hall without any discernible words, 68–78 dB(A)], 7–14 days apart, with counter-balanced presentation of noise conditions across participants of both groups. The results showed widespread cognitive impairment in patients under all conditions, and noise-induced impairments of equal magnitude on specific cognitive functions in both groups. Both patient and healthy participant groups showed significant disruption of delayed verbal recall and recognition by urban and social noise, and of working memory by social noise, relative to the quiet condition. Performance under urban and social noise did not differ significantly from each other for any cognitive measure in either group. We conclude that noise has adverse effects on the verbal and working memory domains in schizophrenia patients and healthy participants. This may be particularly problematic for patients as it worsens their pre-existing cognitive deficits.